2020
DOI: 10.1177/1069072720943838
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Career Preparedness Among Adolescents: Development and Validation of the Career Resources Questionnaire—Adolescent Version

Abstract: Adolescents need to develop career preparedness to successfully transition from school to work. Many factors represent career preparedness, which are difficult to measure comprehensively and economically. We used a career resources framework to assess key aspects of career preparedness among in-school adolescents, and adapted and validated the Career Resources Questionnaire. The questionnaire assesses 12 distinct aspects of career preparedness (i.e., occupational expertise, labor market knowledge, soft skills,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Recent research has demonstrated significant positive relationships between motivational support, levels of self-efficacy, and occupational selection (Guay et al, 2020). Although Marciniak et al (2021) recently attempted to include teachers' motivational support when measuring career-related support in schools, the subscale they used did not address the types of motivational support essential to career development. It should be noted that among the various ways that teachers might support student motivation, only their support for 'goal-setting' was identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has demonstrated significant positive relationships between motivational support, levels of self-efficacy, and occupational selection (Guay et al, 2020). Although Marciniak et al (2021) recently attempted to include teachers' motivational support when measuring career-related support in schools, the subscale they used did not address the types of motivational support essential to career development. It should be noted that among the various ways that teachers might support student motivation, only their support for 'goal-setting' was identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the scale is that it was only validated with a sample of technical education students in mainland China, so the content may not be entirely appropriate for senior secondary school students in Hong Kong. Marciniak et al (2021) developed a different type of instrument-the Career Resources Questionnaire-to investigate adolescents' ability to access different types of psychological and other resources to facilitate their career development. This questionnaire assesses general school support for career guidance, rather than teacher support, and does not include informational support.…”
Section: Evaluating Career-related Teacher Supportmentioning
confidence: 99%
“…An exception to this trend is the Career Resources Questionnaire-Adolescents (CRQ-A) developed by Marciniak et al (2020a) for use with adolescents, which was adapted from the adult Career Resources Questionnaire and based on their work with adolescents on career preparedness. However, CRQ-A was developed in a country where the major educational course decision is made in Grade 9 (aged 14 years) and consequently, the key construct of career decision-making is not included in their measure.…”
Section: Indicators Of the Cedf Factorsmentioning
confidence: 99%
“…The item did not specify if feelings of career preparation were specifically related to STEM careers, although 69.8% of participants reported STEM-related career interests. Career preparation is a very complex concept, and future studies may wish to use potential career-related questionnaires to assess career preparation (Marciniak et al, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%